Mosque Typology in Indonesia Based on Vernacular Architecture - Fairuz Satwiko; Maria Immaculata ririk Winandari; Julindiani Iskandar (Sinektika: Jurnal Arsitektur, 2023)
The mosque which was built in various regions in Indonesia has a variety of its uniqueness. People in Indonesia in general only see that people understand architecture in a mosque only as a domed building or apply Middle Eastern elements only. However, many mosques in Indonesia have applied various Vernaculars to their architectural applications and experienced significant changes to the concept and form of the building. This study aims to find the application of Vernacular facades to 4 mosques in Indonesia, namely the Great Mosque of West Sumatra, the Sunan Ampel Mosque, the Great Mosque of Central Java, and the Grand Mosque of K.H. Hasyim Asyari. The method used is descriptive qualitative with data collection techniques based on journals and articles from the Internet and processed using tables in the form of variables with variables in the form of roofs and mosque wall ornaments. The results of this study are the application of vernacular roof architecture to the mosque in the form of modifications of the local form of each mosque that originates and the application of ornaments on the walls of the mosque which is an adaptation of the local architecture of the local area.